2015
DOI: 10.1186/s13018-015-0249-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patient outcomes in periarticular and intraarticular local anaesthetic infiltration techniques in total knee arthroplasty

Abstract: BackgroundThe use of local infiltration analgesia in the setting of knee arthroplasty is well established. There are no studies to date which have directly compared differences in infiltration techniques. The purpose of this study is to establish if a difference in patient outcomes exists when the infiltrate is injected into the periarticular tissues or directly into the joint.MethodsOne hundred and forty-two consecutive patients waitlisted for primary total knee arthroplasty were enrolled after primary exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Therefore, PAI technique was recommended for performing LIA in TKA. PAI group showed a statistically significant reduction in postoperative VAS pain scores in a previous study [17], which positively correlated with NRS pain scores in our study [26]. In a retrospective study [27], Tietje demonstrated that patients receiving PAI of local anaesthetics in TKA had a noticeable decrease in length of hospital stay and incidence of postoperative nausea and vomiting when compared to patients receiving IAI.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Therefore, PAI technique was recommended for performing LIA in TKA. PAI group showed a statistically significant reduction in postoperative VAS pain scores in a previous study [17], which positively correlated with NRS pain scores in our study [26]. In a retrospective study [27], Tietje demonstrated that patients receiving PAI of local anaesthetics in TKA had a noticeable decrease in length of hospital stay and incidence of postoperative nausea and vomiting when compared to patients receiving IAI.…”
Section: Discussionsupporting
confidence: 80%
“…To show a clinically important difference of 1.3 [25] in NRS pain score between PAI group and IAI group, with a standard deviation of 2.0 according to the published article [17], a power 0.90 and a two-tailed significance of <0.05, each group required 49 subjects.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…There were several trials comparing intra-articular infiltration with periarticular infiltration. Andersen et al [25] and Perret et al [26] concluded no clear statistically significant benefit with either technique. On the contrary, Tsuyoshi Nakai et al [27] showed the level of pain control was higher in periarticular infiltration than in intra-articular infiltration.…”
Section: Discussionmentioning
confidence: 96%
“…This technique soaks the cortical bone and appears to provide enough anesthesia to permit trocar rotational advancement. Approximately 2-5 ccs of 2% lidocaine seemed to reduce the noxious stimulation, much like the periarticular infiltration analgesia used for the total knee arthroplasties (18). Next, the bone drill was inserted to create a cortical window in the vertebral body.…”
Section: Office-based Pbk Surgical Proceduresmentioning
confidence: 99%